Sapphire polishing solution as well as preparation method and application thereof

By adding components such as rigid double helix, low-charge polysaccharides, and nonionic cellulose ethers to the sapphire polishing slurry, a stable three-dimensional network structure is formed, which solves the problem of reduced suspension performance under strong alkali and high ionic strength, and achieves a highly efficient sapphire polishing effect.

CN121319793APending Publication Date: 2026-01-13QUZHOU BOLAINARUN ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511608098.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing sapphire polishing slurries exhibit reduced suspension properties under strong alkalinity and high ionic strength, leading to slurry sedimentation and agglomeration, which affects the polishing effect.

Method used

The product uses a combination of alumina powder, dispersant, suspending agent, pH adjuster and lubricant. The rigid double helix and low charge characteristics of the suspending agent form a stable three-dimensional network structure in a strongly alkaline environment. Combined with the high hydration and steric hindrance effect of nonionic cellulose ether, the suspension performance is maintained and it becomes thinner under high shear to facilitate polishing.

Benefits of technology

Under strong alkalinity and high ionic strength, sapphire polishing slurry maintains excellent suspension performance and dispersion stability, achieving high removal efficiency and excellent polishing effect with low surface roughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005671328150000111
    Figure BDA0005671328150000111
Patent Text Reader

Abstract

The invention relates to the technical field of grinding and polishing, in particular to a sapphire polishing solution as well as a preparation method and application thereof. The sapphire polishing solution comprises the following components in parts by weight: 20-30 wt% of alumina powder, 0.1-1 wt% of a dispersing agent, 0.01-1 wt% of a suspension additive, 1-10 wt% of a pH regulator, 0.1-3 wt% of a lubricant and the balance of water, the suspension auxiliary agent is selected from one or more of nonionic cellulose ether and polysaccharide with rigid double-helix, low-charge and acetyl-free structural characteristics. The grinding particles of the sapphire polishing solution are excellent in suspension performance and high in dispersion stability under strong base and high ionic strength; the sapphire wafer polishing solution has high polishing removal efficiency and excellent surface quality (low roughness Ra) on sapphire wafers under the conditions of strong base and high ionic strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of grinding and polishing technology, and in particular to a sapphire polishing slurry, its preparation method, and its application. Background Technology

[0002] Sapphire (primarily composed of aluminum oxide) possesses excellent physical and chemical properties, extremely high hardness and wear resistance, excellent thermal stability, good chemical inertness, and outstanding optical properties, and it also exhibits high lattice compatibility with GaN. In recent years, the application of sapphire materials has expanded from traditional LED substrates to multiple fields such as semiconductors, optics, consumer electronics, and quantum technology. With the development of emerging industries such as Micro-LED, 5G, and AR / VR, its strategic importance will continue to rise. However, all of these application areas place high demands on the surface quality of sapphire.

[0003] Alumina sapphire polishing slurry is a core material for achieving ultra-precision machining and atomic-level smoothness of sapphire surfaces. In existing technologies, alumina polishing slurry is often used to polish sapphire substrates through a chemimechanical synergy, efficiently removing surface defects and achieving atomic-level smoothness (roughness Ra < 0.4 nm). However, alumina particles have a large specific surface area and high surface energy, making them prone to agglomeration. Large agglomerates can affect the stability of the polishing process, reduce the removal rate and roughness, and even cause unacceptable scratches. Therefore, excellent suspension properties and dispersion stability are crucial factors in ensuring high-efficiency removal rates and excellent surface polishing effects of alumina slurry.

[0004] One way to improve the removal efficiency of sapphire polishing slurries is to accelerate the softening of the sapphire surface, which can be achieved by increasing the content of inorganic alkali in the sapphire polishing slurry. In recent years, the pH value of sapphire polishing slurries has been increased to 12-14. However, the increase in inorganic alkali content leads to an increase in the alkalinity and ionic strength of the sapphire polishing slurry. Under high alkalinity and high ionic strength conditions, alumina abrasive particles are difficult to maintain their suspension properties for a long time, and are prone to sedimentation and agglomeration, thus affecting polishing performance. For example, patent CN115216224A discloses a sapphire polishing slurry, its preparation method, and its application. The sapphire polishing slurry comprises: 1-30% alumina abrasive, 0.5-10% alkaline regulator, 0.5-15% aluminum ion complexing agent, 0.01-3% surfactant, 0.01-1% thixotropic agent, and the remainder being pure water. The thixotropic agent is selected from one or more of fumed silica, fumed aluminum oxide, magnesium aluminum silicate, lithium magnesium silicate, and sodium carboxymethyl cellulose. The pH value of the sapphire polishing slurry is 12-14. Fumed silica and fumed aluminum oxide have a large specific surface area, approximately 100-300 m². 2 / g, with strong water absorption; magnesium aluminum silicate and magnesium lithium silicate have unique three-dimensional chain structures and special needle-like and rod-shaped crystal structures, exhibiting strong water absorption. In aqueous media, they form a card-like associated network structure, possessing strong moisturizing properties; thixotropic sodium carboxymethyl cellulose macromolecules interact to form a three-dimensional structure, exhibiting strong water absorption and thickening and moisturizing effects. Therefore, the added thixotropic agent prevents caking while also preventing fine particles from adhering firmly to the sapphire surface, facilitating the cleaning of the sapphire surface;

[0005] In the aforementioned sapphire polishing slurry, the thixotropic mechanism of fumed silica and fumed alumina involves the formation of a hydrogen bond network through surface hydroxyl groups. However, under alkaline conditions (pH>9), the surface hydroxyl groups react with OH- ions to generate negatively charged ions. Because like charges repel each other between particles, the hydrogen bonds that form the three-dimensional network are destroyed, leading to the collapse of the entire gel structure and a decrease or even disappearance of the suspension effect. Magnesium aluminum silicate and magnesium lithium silicate can form a "house-of-cards" structure through the swelling and separation of lamellar layers, constructing a robust three-dimensional network. However, high ionic strength inhibits lamellar swelling, weakening the suspension effect. Sodium carboxymethyl cellulose is an ionic thickener; under weakly alkaline conditions, -COOH transforms into -COO-, the molecular chains extend, and the viscosity reaches its maximum. When the alkali concentration is very high (e.g., pH>12, especially in the presence of high-concentration electrolytes such as NaOH or KOH), excessive Na... + It will shield the -COO- charge, destroy its hydration layer, causing the polymer chains to dehydrate and curl, eventually precipitating out of the water and losing their thickening ability.

[0006] In summary, when the pH value of the sapphire polishing solution described in patent CN115216224A is between 12 and 14, the suspension performance of the sapphire polishing solution decreases under strong alkalinity and high ionic strength, and the alumina slurry settles and agglomerates, thereby reducing the effectiveness of the sapphire surface polishing treatment.

[0007] Therefore, there is an urgent need to develop a sapphire polishing slurry with excellent suspension properties and stability under strong alkalinity and high ionic strength to ensure its stability and polishing effect when used for sapphire polishing. Summary of the Invention

[0008] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a sapphire polishing slurry, its preparation method, and its application. The sapphire polishing slurry described in this application solves the problem in the prior art where the suspension performance of the sapphire polishing slurry decreases under strong alkaline and high ionic strength conditions, leading to sedimentation and agglomeration of the slurry, thus reducing the polishing effect on the sapphire surface. In this application, the strong alkaline environment refers to pH > 12, and the high ionic strength refers to an ionic strength greater than 1 mol / L.

[0009] To achieve the above and other related objectives, the present invention is obtained through the following technical solution.

[0010] The first aspect of this invention discloses a sapphire polishing slurry, comprising the following components in parts by weight: 20-30 wt% alumina powder, 0.1-1 wt% dispersant, 0.01-1 wt% suspending agent, 1-10 wt% pH adjuster, 0.1-3 wt% lubricant, and the balance being water; the suspending agent is selected from one or more polysaccharides and nonionic cellulose ethers that possess the structural characteristics of rigid double helix, low charge, and acetyl-free structure. The components of the sapphire polishing slurry work synergistically to maintain a good three-dimensional network structure even under strong alkalinity and high ionic strength; it exhibits high suspension at low shear to prevent alumina particle sedimentation; and it thins out at high shear, facilitating flow and polishing operations.

[0011] The content of the alumina powder can be 20-21 wt%, 21-22 wt%, 22-23 wt%, 23-24 wt%, 24-25 wt%, 25-26 wt%, 26-27 wt%, 27-28 wt%, 28-29 wt%, or 29-30 wt%.

[0012] The content of the dispersant can be 0.1–0.2 wt%, 0.2–0.3 wt%, 0.3–0.4 wt%, 0.4–0.5 wt%, 0.5–0.6 wt%, 0.6–0.7 wt%, 0.7–0.8 wt%, 0.8–0.9 wt%, or 0.9–1.0 wt%.

[0013] The content of the suspending agent may be 0.01–0.015 wt%, 0.015–0.02 wt%, 0.02–0.1 wt%, 0.1–0.15 wt%, 0.15–0.2 wt%, 0.2–0.3 wt%, 0.3–0.4 wt%, 0.4–0.5 wt%, 0.5–0.6 wt%, 0.6–0.7 wt%, 0.7–0.8 wt%, or 0.8–0.9 wt%.

[0014] The content of the pH adjuster can be 1-2 wt%, 2-3 wt%, 3-4 wt%, 4-5 wt%, 5-6 wt%, 6-7 wt%, 7-8 wt%, 8-9 wt%, or 9-10 wt%.

[0015] The content of the lubricant can be 0.1-0.2 wt%, 0.2-0.3 wt%, 0.3-0.4 wt%, 0.4-0.5 wt%, 0.5-1 wt%, 1-1.5 wt%, 1.5-2 wt%, 2-2.5 wt%, or 2.5-3 wt%.

[0016] Preferably, the suspending agent comprises a mixture of a polysaccharide with a rigid double helix structure, low charge, and acetyl-free structure, and a nonionic cellulose ether.

[0017] Preferably, the nonionic cellulose ether is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl cellulose, and hydroxyethyl ethyl cellulose.

[0018] Preferably, the polysaccharide possessing the structural characteristics of a rigid double helix, low charge, and no acetyl is selected from one or more of the following: gentian gum and its modified products, gentian gum and its modified products, and gentian gum and its modified products.

[0019] In this application, the term "low charge" refers to the fact that the polysaccharide has a small number of charged groups (such as carboxylate -COO-) in its molecular structure, especially that the side chain contains almost no charged groups, while the main chain contains only a small number of -COO- groups.

[0020] Preferably, the alumina powder is α-alumina.

[0021] Preferably, the D of the alumina powder 50 The diameter is 0.3–3 μm, D 100 <10μm. The D of the alumina powder as described above... 50 The micrometers can be 0.3–0.5 μm, 0.5–0.7 μm, 0.7–0.9 μm, 0.9–1 μm, 1–1.4 μm, 1.4–1.8 μm, 1.8–2.2 μm, 2.2–2.6 μm, or 2.6–3 μm.

[0022] The alumina powder acts as a grinding agent to improve the removal rate. If D 50 If the polishing thickness is less than 0.3 μm, the polishing efficiency and effect will decrease; if D 50 Greater than 3μm and / or D 100 If the size is greater than 10μm, unacceptable scratches are likely to be generated on the sapphire surface, affecting the surface quality of the sapphire.

[0023] Preferably, the dispersant is selected from one or more of sodium polyacrylate, acrylic acid-maleic acid copolymer, sodium hexametaphosphate, and sodium tripolyphosphate. The dispersant allows the alumina powder to be better dispersed in the sapphire polishing slurry, preventing alumina powder agglomeration.

[0024] Preferably, the pH adjuster is selected from one or more of potassium hydroxide, sodium hydroxide, and triethanolamine. The pH adjuster can enhance the chemical reaction between the sapphire polishing solution and the sapphire wafer surface, thereby increasing the removal rate.

[0025] Preferably, the lubricant is selected from one or more of PEG, polyglycerol-10, triethylene glycol, glycerol, triethanolamine borate, and diethanolamine borate. The lubricant reduces friction between the abrasive particles and the workpiece surface during polishing, preventing scratches and achieving a smooth surface.

[0026] More preferably, the molecular weight of the PEG is 190–440 g / mol. For example, it can be 190–200 g / mol, 200–210 g / mol, 210–250 g / mol, 250–300 g / mol, 300–330 g / mol, 330–360 g / mol, 360–380 g / mol, 380–400 g / mol, 400–420 g / mol, or 420–440 g / mol.

[0027] Preferably, the pH value of the sapphire polishing solution is 12-14. For example, it can be 12-12.5, 12.5-13, 13-13.5, or 13.5-14. Within this pH range, the sapphire polishing solution achieves the best synergistic effect of mechanical polishing and chemical action on sapphire. If the pH is below 12, the chemical action is weak, the softening rate of the sapphire surface is slow, making mechanical removal difficult and resulting in low polishing efficiency. If the pH is above 14, the chemical action is too strong; not only will the sapphire surface be softened, but the alumina powder itself will also be corroded or softened, leading to "passivation" of the alumina powder, loss of cutting ability, and a sharp decrease in the polishing rate.

[0028] The second aspect of the present invention discloses a method for preparing the sapphire polishing fluid as described above, the method comprising the following steps: stirring and mixing the raw material components.

[0029] Preferably, the mixing sequence is as follows: first, water, alumina powder, dispersant, and lubricant are mixed evenly; then, an aqueous solution of suspending agent is added and mixed evenly; finally, a pH adjuster is added and mixed evenly to adjust the pH of the mixture to 12-14.

[0030] Preferably, the linear velocity of the stirring mixture is 3-10 m / s. For example, the linear velocity of the stirring mixture can be 3-4 m / s, 4-5 m / s, 5-6 m / s, 6-7 m / s, 7-8 m / s, 8-9 m / s, or 9-10 m / s.

[0031] More preferably, the method for preparing the aqueous solution of the suspending agent includes: dispersing the suspending agent in water, and fully hydrolyzing and swelling it.

[0032] More preferably, the linear velocity of the suspending agent dispersed in water is 3-10 m / s. For example, the linear velocity of the suspending agent dispersed in water can be 3-4 m / s, 4-5 m / s, 5-6 m / s, 6-7 m / s, 7-8 m / s, 8-9 m / s, or 9-10 m / s.

[0033] In this application, the linear velocity refers to the circumferential velocity of the outermost edge of the stirrer blade.

[0034] More preferably, the concentration of the aqueous solution of the suspending agent is 0.5–2 wt%. For example, it can be 0.5–0.6 wt%, 0.6–0.7 wt%, 0.7–0.8 wt%, 0.8–0.9 wt%, 0.9–1.0 wt%, 1.0–1.1 wt%, 1.1–1.2 wt%, 1.2–1.3 wt%, 1.3–1.4 wt%, 1.4–1.5 wt%, 1.5–1.6 wt%, 1.6–1.7 wt%, 1.7–1.8 wt%, 1.8–1.9 wt%, or 1.9–2.0 wt%.

[0035] More preferably, the time for mixing the aqueous solution containing the suspending agent is 45–75 min. For example, it can be 45–50 min, 50–55 min, 55–60 min, 60–65 min, 65–70 min, or 70–75 min.

[0036] More preferably, the mixing time for adding the pH adjuster is 45–75 min. For example, it can be 45–50 min, 50–55 min, 55–60 min, 60–65 min, 65–70 min, or 70–75 min.

[0037] More preferably, after adjusting the pH of the mixture to 12-14, the process further includes the steps of dispersing, filtering, and filling.

[0038] More preferably, the continued dispersion time is 90–180 min. For example, it can be 90–100 min, 100–110 min, 110–120 min, 120–130 min, 130–140 min, 140–150 min, 150–160 min, 160–170 min, or 170–180 min.

[0039] The third aspect of the present invention also discloses the application of the sapphire polishing slurry as described above in polishing sapphire.

[0040] The fourth aspect of the present invention also discloses the use of a suspending agent in improving the suspension performance of sapphire polishing fluid, wherein the suspending agent is selected from one or more of nonionic cellulose ethers and polysaccharides that have the structural characteristics of rigid double helix, low charge, and no acetyl.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The sapphire polishing slurry disclosed in this application is obtained through the synergistic effect of its components. It is obtained by first swelling the suspending agent to form an aqueous solution of the suspending agent, and then mixing it with the remaining raw materials and adding alkali. Under strong alkali and high ionic strength, it can maintain suspension performance for a long time. Furthermore, under strong alkali and high ionic strength, the sapphire polishing slurry achieves high removal efficiency and excellent polishing effect (low roughness Ra) on polished sapphire. Detailed Implementation

[0043] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.

[0044] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the respective manufacturers.

[0045] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or equivalent to those described, apparatus, and materials in the embodiments of this invention may be used to implement the present invention.

[0046] In this application, addressing the technical problem that existing sapphire polishing slurries suffer from reduced suspension performance under strong alkalinity and high ionic strength, leading to sedimentation and agglomeration of the slurry and consequently diminishing the polishing effect on sapphire surfaces, the applicant provides a sapphire polishing slurry, its preparation method, and its applications. The sapphire polishing slurry described in this application exhibits excellent suspension performance and high dispersion stability under high alkalinity and high ionic strength conditions, enabling high removal efficiency and excellent surface quality for sapphire wafer polishing even under these conditions.

[0047] Specifically, this invention provides a specific sapphire polishing slurry and its preparation method. The sapphire polishing slurry comprises the following components by weight: 20-30 wt% alumina powder, 0.1-1 wt% dispersant, 0.01-1 wt% suspending agent, 1-10 wt% pH adjuster, 0.1-3 wt% lubricant, and the balance being water. The suspending agent is selected from one or more polysaccharides and nonionic cellulose ethers that possess rigid double helix structure, low charge, and acetyl-free structural characteristics. The components of the sapphire polishing slurry work synergistically to maintain a good three-dimensional network structure even under strong alkalinity and high ionic strength. It exhibits high suspension at low shear to prevent alumina particle sedimentation and thins out at high shear, facilitating flow and polishing operations.

[0048] The content of each raw material component in this application can be adjusted according to actual polishing and production needs.

[0049] The content of the alumina powder can be 20-21 wt%, 21-22 wt%, 22-23 wt%, 23-24 wt%, 24-25 wt%, 25-26 wt%, 26-27 wt%, 27-28 wt%, 28-29 wt%, or 29-30 wt%.

[0050] The content of the dispersant can be 0.1–0.2 wt%, 0.2–0.3 wt%, 0.3–0.4 wt%, 0.4–0.5 wt%, 0.5–0.6 wt%, 0.6–0.7 wt%, 0.7–0.8 wt%, 0.8–0.9 wt%, or 0.9–1.0 wt%.

[0051] The content of the suspending agent may be 0.01–0.015 wt%, 0.015–0.02 wt%, 0.02–0.1 wt%, 0.1–0.15 wt%, 0.15–0.2 wt%, 0.2–0.3 wt%, 0.3–0.4 wt%, 0.4–0.5 wt%, 0.5–0.6 wt%, 0.6–0.7 wt%, 0.7–0.8 wt%, or 0.8–0.9 wt%.

[0052] The content of the pH adjuster can be 1-2 wt%, 2-3 wt%, 3-4 wt%, 4-5 wt%, 5-6 wt%, 6-7 wt%, 7-8 wt%, 8-9 wt%, or 9-10 wt%.

[0053] The content of the lubricant can be 0.1-0.2 wt%, 0.2-0.3 wt%, 0.3-0.4 wt%, 0.4-0.5 wt%, 0.5-1 wt%, 1-1.5 wt%, 1.5-2 wt%, 2-2.5 wt%, or 2.5-3 wt%.

[0054] In this application, the mechanism by which the sapphire polishing slurry maintains excellent suspension performance for a long time under strong alkalinity and high ionic strength is as follows:

[0055] When one or more nonionic cellulose ethers are selected as the suspending agent, the side chains of the nonionic cellulose ethers are hydrophilic hydroxyethyl (-CH2-CH2-OH) or hydroxypropyl (-CH2-CHOH-CH3) and methoxy (-O-CH3). Because they do not carry ionic charges, their dissolution and thickening are not affected by strong bases or high ionic strength in the system. After dissolution, the highly hydrated and relatively long molecular chains restrict water flow through physical chain entanglement and steric hindrance, thereby achieving high suspension performance.

[0056] When the suspending agent is a polysaccharide with the structural characteristics of a rigid double helix, low charge, and no acetyl, the suspension performance of the polishing solution is improved through the following physical pathway after the addition of a pH adjuster, relying on its structural characteristics of a rigid double helix, low charge, and no acetyl. Specifically:

[0057] ① Carboxyl group ionization enhances the repulsive force between molecular chains. In a strongly alkaline environment (e.g., pH>9), the carboxylic acid groups in the repeating units of the main chain completely ionize into —COO-, significantly increasing the negative charge density of the molecular chain. The increased electrostatic repulsion between chain segments leads to a change in polymer conformation from coiled to extended, resulting in an increase in hydrodynamic volume, which macroscopically manifests as an increase in viscosity.

[0058] ② The side-chain protection effect delays degradation. Unlike other polysaccharide thickeners, its -COO - Only located in the main chain, the side chains contain no charged groups. Intramolecular hydrogen bonds maintain the double helix – a rigid rod. OH - Difficult to insert into the backbone; this "side-chain shielding" structure can partially protect the main chain from OH in strong bases. - Direct attack slows down the alkaline hydrolysis rate of glycosidic bonds.

[0059] This makes the thickening effect last longer.

[0060] When the suspending agent is a mixture of nonionic cellulose ether and polysaccharide with structural characteristics of rigid double helix, low charge, and no acetyl, the suspension performance is improved through the following pathways:

[0061] ① The long-chain structure of nonionic cellulose ethers creates steric hindrance, reducing OH groups. - Direct attack on the backbone of polysaccharides possessing structural characteristics such as rigid double helix, low charge, and no acetyl; the viscosity of the system increases after compounding, reducing OH... - The diffusion rate is reduced, slowing down the degradation of polysaccharides that possess the structural characteristics of a rigid double helix, low charge, and no acetyl.

[0062] ② Nonionic cellulose ethers form a new hydrogen bond network with polysaccharides that have the structural characteristics of rigid double helix, low charge, and no acetyl, which compensates for the hydrogen bonds that are destroyed in a strong alkaline environment and indirectly enhances the structural stability.

[0063] Synergistic effect of pH adjusters and suspending agents: In NaOH / KOH solution, Na... + / K + The shielding-COO-repulsion, with rods approaching each other to form "salt bridge" nodes, allows the interchain repulsion induced by high charge density to be transformed into new network support forces, thereby increasing the network density and achieving excellent suspension performance under high alkalinity and high ionic strength.

[0064] In one specific embodiment, the polysaccharide possessing the structural characteristics of a rigid double helix, low charge, and no acetyl is selected from one or more of the following: gentian gum and its modified products, gentian gum and its modified products, and gentian gum and its modified products.

[0065] In this application, "low charge" refers to the fact that the polysaccharide has a small number of charged groups (such as carboxylate -COO-) in its molecular structure, especially that the side chain contains almost no charged groups, while the main chain contains only a small number of -COO- groups.

[0066] It should be noted that the suspension aids claimed in this application include, but are not limited to, nonionic cellulose ethers, polysaccharides with the structural characteristics of rigid double helix, low charge, and no acetyl, compounds that satisfy the structural characteristics of rigid double helix, low charge, and no acetyl or satisfy the requirement of hydrophilic side chains but without ionic charge, and whose dissolution and thickening are not affected by strong base and high ionic strength of the system.

[0067] In one specific embodiment, the nonionic cellulose ether is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl cellulose, and hydroxyethyl ethyl cellulose.

[0068] In one specific embodiment, the alumina powder is α-alumina. α-alumina has high hardness and low abrasion, making it suitable for polishing sapphire.

[0069] In one specific embodiment, the D of the alumina powder 50 The diameter is 0.3–3 μm, D 100 <10μm. The D of the alumina powder as described above... 50 The alumina powder can be 0.3–0.5 μm, 0.5–0.7 μm, 0.7–0.9 μm, 0.9–1 μm, 1–1.4 μm, 1.4–1.8 μm, 1.8–2.2 μm, 2.2–2.6 μm, or 2.6–3 μm. The alumina powder acts as a grinding agent, thereby increasing the removal rate. If D50 If the polishing thickness is less than 0.3 μm, the polishing efficiency and effect will decrease; if D 50 Greater than 3μm and / or D 100 If the size is greater than 10μm, unacceptable scratches are easily generated on the sapphire surface, affecting the polishing effect.

[0070] In one specific embodiment, the dispersant is selected from one or more of sodium polyacrylate, acrylic acid-maleic acid copolymer, sodium hexametaphosphate, and sodium tripolyphosphate. The dispersant allows the alumina powder to be better dispersed in the sapphire polishing slurry, preventing powder agglomeration. It should be noted that the selection of the dispersant includes, but is not limited to, the examples listed above; the dispersant can be any compound that can disperse alumina powder in the sapphire polishing slurry.

[0071] In one specific embodiment, the pH adjuster is selected from one or more of potassium hydroxide, sodium hydroxide, and triethanolamine. The pH adjuster can enhance the chemical reaction between the sapphire polishing solution and the sapphire wafer surface, thereby increasing the removal rate. It should be noted that the selection of the pH adjuster includes, but is not limited to, the examples listed above; the pH adjuster can be any compound capable of increasing alkalinity.

[0072] In one specific embodiment, the lubricant is selected from one or more of PEG200, PEG400, polyglycerol-10, triethylene glycol, glycerol, triethanolamine borate, and diethanolamine borate. The lubricant reduces friction between the abrasive and the workpiece surface during polishing, prevents scratches, and achieves a smooth surface. It should be noted that the selection of the lubricant includes, but is not limited to, the examples listed above; the lubricant can be any compound capable of reducing friction between the abrasive and the workpiece surface.

[0073] In one specific embodiment, the pH value of the sapphire polishing solution is 12-14. For example, it can be 12-12.5, 12.5-13, 13-13.5, or 13.5-14. Within this pH range, the sapphire polishing solution achieves the best synergistic effect of mechanical polishing and chemical action on sapphire. If the pH is below 12, the chemical action is weak, the softening rate of the sapphire surface is slow, leading to difficulties in mechanical removal and low efficiency. If the pH is above 14, the chemical action is too strong; not only will the sapphire surface be softened, but the alumina abrasive itself will also be corroded or softened, causing the abrasive to become "passivated," lose its cutting ability, and the polishing rate drops sharply.

[0074] In this application, the modified products refer to derivatives of ductile gum, Wenlun gum, and Brunei gum obtained through chemical modification, physical / composite modification, or biological / genetic modification.

[0075] This invention provides a specific method for preparing a sapphire polishing slurry, the method comprising the following steps: stirring and mixing the raw material components.

[0076] In one specific embodiment, the mixing sequence is as follows: first, water, alumina powder, dispersant, and lubricant are mixed evenly; then, an aqueous solution of suspending agent is added and mixed evenly; finally, a pH adjuster is added and mixed evenly to adjust the pH of the mixture to 12-14.

[0077] In one specific embodiment, the linear velocity of the stirring and mixing is 3-10 m / s. For example, the linear velocity of the stirring and mixing can be 3-4 m / s, 4-5 m / s, 5-6 m / s, 6-7 m / s, 7-8 m / s, 8-9 m / s, or 9-10 m / s. It should be noted that the linear velocity of the stirring and mixing can be adjusted by the actual equipment used for dispersion and its power, as long as the effect of uniformly dispersing the raw materials is achieved. For example, when the dispersion time is shorter / the agitator blades are shorter, the rotation speed is faster; when the dispersion time is longer / the agitator blades are longer, the rotation speed is slower.

[0078] In a more specific embodiment, the method for preparing the aqueous solution of the suspending agent includes: dispersing the suspending agent in water, and fully hydrolyzing and swelling it.

[0079] In a further specific embodiment, the linear velocity of the suspending agent dispersed in water is 3-10 m / s. For example, the linear velocity of the suspending agent dispersed in water can be 3-4 m / s, 4-5 m / s, 5-6 m / s, 6-7 m / s, 7-8 m / s, 8-9 m / s, or 9-10 m / s.

[0080] In a more specific embodiment, the concentration of the aqueous solution of the suspending agent is 0.5–2 wt%. For example, it can be 0.5–0.6 wt%, 0.6–0.7 wt%, 0.7–0.8 wt%, 0.8–0.9 wt%, 0.9–1.0 wt%, 1.0–1.1 wt%, 1.1–1.2 wt%, 1.2–1.3 wt%, 1.3–1.4 wt%, 1.4–1.5 wt%, 1.5–1.6 wt%, 1.6–1.7 wt%, 1.7–1.8 wt%, 1.8–1.9 wt%, or 1.9–2.0 wt%. It should be noted that the concentration of the aqueous solution of the suspending agent can be adjusted according to actual needs or operation, as long as the suspending agent is sufficiently hydrolyzed and swollen.

[0081] In a more specific embodiment, the time for mixing the aqueous solution containing the suspending agent is 45–75 min. For example, it can be 45–50 min, 50–55 min, 55–60 min, 60–65 min, 65–70 min, or 70–75 min.

[0082] In a more specific embodiment, the mixing time for adding the pH adjuster is 45–75 min. For example, it can be 45–50 min, 50–55 min, 55–60 min, 60–65 min, 65–70 min, or 70–75 min.

[0083] In a more specific embodiment, after adjusting the pH of the mixture to 12-14, the process further includes steps of dispersion, filtration, and filling.

[0084] In a further specific embodiment, the continued dispersion time is 90–180 min. For example, it can be 90–100 min, 100–110 min, 110–120 min, 120–130 min, 130–140 min, 140–150 min, 150–160 min, 160–170 min, or 170–180 min.

[0085] It should be noted that the dispersion or mixing time mentioned above can be adjusted according to the actual equipment used for dispersion and its power, as long as the effect of uniform dispersion of raw materials can be achieved. For example, when the linear speed is faster, the dispersion time is shorter; when the linear speed is slower, the dispersion time is longer.

[0086] The technical solution and effects of the present invention will be further illustrated and explained through the following specific embodiments and implementation effects.

[0087] The following embodiments of this application:

[0088] D 50 and D 100 The particle size was obtained using a Malvern particle size analyzer and Zetasizer Advance Series-Lab.

[0089] The suspension rate is calculated using the following formula: Suspension rate = Height of slurry layer / Total height of solution; In this application, when testing the suspension rate, the sapphire polishing liquid is placed in a uniform container such as a measuring cylinder or beaker, left to stand for a corresponding time, and the height of the suspended portion and the total height of the solution are measured, wherein the height of the suspended portion is the slurry layer.

[0090] Ionic strength I is calculated using the following formula: Ionic strength = 1 / 2 × Σ(concentration × charge) 2 )

[0091] Example 1

[0092] In this embodiment, a specific sapphire polishing slurry and its preparation method are provided. The preparation method includes the following steps:

[0093] 1) Weigh out 625g of pure water and 200g of D respectively. 50 0.8μm α-alumina powder, 5g sodium hexametaphosphate, and 20g PEG200 were stirred evenly at a stirring linear speed of 5m / s to obtain a premixed solution.

[0094] 2) Disperse 0.5g of iodized gum and 0.5g of hydroxyethyl cellulose in 99g of pure water at a stirring speed of 5m / s, and allow them to fully hydrolyze and swell to prepare an aqueous solution of 1wt% suspension aid.

[0095] 3) Mix the premixed liquid with the aqueous solution of the suspending agent and stir for 60 minutes at a stirring linear speed of 5 m / s.

[0096] 4) Slowly add 0.1g NaOH at a stirring speed of 5m / s and stir for 60min.

[0097] 5) Add 49.9 g NaOH slowly at a stirring speed of 5 m / s, and the pH of the solution is 13.76.

[0098] 6) Continue dispersing for 120 minutes at a stirring linear speed of 5 m / s, and then filter to obtain the sapphire polishing slurry.

[0099] Example 2

[0100] In this embodiment, a specific sapphire polishing slurry and its preparation method are provided. The preparation method includes the following steps:

[0101] 1) Weigh out 570g of pure water and 250g of alumina powder D respectively. 50 1.5μm, 10g sodium polyacrylate 445N and 10g triethylene glycol were stirred evenly at a stirring linear speed of 5m / s to obtain a premix.

[0102] 2) Disperse 1g of Wenlun gum and 0.5g of hydroxyethyl cellulose in 98.5g of pure water at a stirring speed of 5m / s, and fully hydrolyze and swell to prepare a 1.5wt% aqueous solution of suspension aid.

[0103] 3) Mix the premixed liquid with the aqueous solution of the suspending agent and stir for 60 minutes at a stirring linear speed of 5 m / s.

[0104] 4) Slowly add 0.1g KOH at a stirring speed of 5m / s and stir for 60min.

[0105] 5) Slowly add 59.9g KOH at a stirring speed of 5m / s, resulting in a pH of 13.98.

[0106] 6) Continue dispersing for 120 minutes at a stirring linear speed of 5 m / s, and then filter to obtain the sapphire polishing slurry.

[0107] Example 3

[0108] In this embodiment, a specific sapphire polishing slurry and its preparation method are provided. The preparation method includes the following steps:

[0109] 1) Weigh out 522g of pure water and 300g of alumina powder D respectively. 50 2 μm, 3 g of acrylic acid-maleic acid copolymer SP88, and 5 g of triethanolamine borate were stirred evenly at a stirring speed of 5 m / s to obtain a premix.

[0110] 2) Disperse 1g of Brunei gum and 1g of hydroxypropyl methylcellulose in 98g of pure water at a stirring speed of 5m / s, and allow them to fully hydrolyze and swell to prepare a 2wt% aqueous solution of suspension aid.

[0111] 3) Mix the premixed liquid with the aqueous solution of the suspending agent and stir for 60 minutes at a stirring linear speed of 5 m / s.

[0112] 4) Add 2g of triethanolamine at a stirring speed of 5m / s and stir for 60min.

[0113] 5) Slowly add 50g NaOH and 18g triethanolamine at a stirring speed of 5m / s, with a pH of 13.84.

[0114] 6) Continue dispersing for 120 minutes at a stirring linear speed of 5 m / s, and then filter to obtain the sapphire polishing slurry.

[0115] Example 4

[0116] In this embodiment, a specific sapphire polishing liquid and its preparation method are provided. The difference between the preparation method and that in Example 1 is that 0.5g of precipitant and 0.5g of hydroxyethyl cellulose are replaced with 1g of precipitant.

[0117] Example 5

[0118] In this embodiment, a specific sapphire polishing fluid and its preparation method are provided. The difference between the preparation method and that in Example 2 is that 1g of Werlen gum and 0.5g of hydroxyethyl cellulose are replaced with 1.5g of Werlen gum.

[0119] Example 6

[0120] In this embodiment, a specific sapphire polishing fluid and its preparation method are provided. The difference between the preparation method and that in Example 1 is that 1g of Brunei gum and 1g of hydroxypropyl methylcellulose are replaced with 2g of Brunei gum.

[0121] Example 7

[0122] In this embodiment, a specific sapphire polishing fluid and its preparation method are provided. The difference between the preparation method and that in Example 1 is that 0.5g of precipitant and 0.5g of hydroxyethyl cellulose are replaced with 1g of hydroxyethyl cellulose.

[0123] Comparative Example 1

[0124] In this comparative example, according to patent CN115216224A, a specific sapphire polishing solution and its preparation method are provided, the preparation method including the following steps:

[0125] 1) Weigh 200g of α-Al2O3, 10g of sodium ethylenediaminetetramethylenephosphonate, 10g of disodium ethylenediaminetetraacetate, 10g of potassium sodium tartrate, 0.5g of a sulfonic acid-containing polymer sodium salt, 0.5g of sodium methylenebisnaphthalene sulfonate, 0.5g of fumed silica, 0.3g of magnesium aluminum silicate, 0.2g of sodium carboxymethyl cellulose, 50g of NaOH and 718g of pure water, and stir evenly to obtain a slurry.

[0126] 2) The slurry was passed through a sand mill and ball-milled at 1500 rpm for 2 hours. D was then measured. 50 It is 0.78μm, D 100 It is 4.50μm.

[0127] Comparative Example 2

[0128] In this comparative example, a specific sapphire polishing slurry and its preparation method are provided. The difference between the preparation method of the sapphire polishing slurry and that in Example 1 is that 0.5g of precipitant and 0.5g of hydroxyethyl cellulose are replaced with 0.5g of fumed silica, 0.3g of magnesium aluminum silicate, and 0.2g of sodium carboxymethyl cellulose, and are directly mixed with the rest of the original.

[0129] The sapphire polishing solutions obtained in Examples 1-7 and Comparative Examples 1-2 were left to stand at 25°C and 50°C for 24 hours and 7 days, respectively, and the suspension rate of the sapphire polishing solutions was tested. The results are shown in the table below:

[0130] Table 1

[0131]

[0132] Test result data explanation:

[0133] In Example 1 and Comparative Example 1, the alumina powder particle size and content were equal, and the amount of pH adjuster added was equal. Under strong alkalinity (pH > 13.5) and strong ionic strength (ionic strength I > 1.3 mol / L), the long-term suspension rate of Example 1 was above 90%, while that of the Comparative Example was 30%. The long-term suspension rates of the other examples were above 65%. Among them, the suspension rates of the sapphire polishing solutions in Examples 1-3, which were compounded with nonionic cellulose ether and polysaccharides with rigid double helix, low charge, and acetyl-free structural characteristics, were higher than those in Examples 4-7, which used the above two types of suspension aids alone.

[0134] It is evident that the sapphire polishing solution of the present invention can maintain excellent suspension properties for a long time under high alkalinity and high ionic strength conditions.

[0135] The applicant further used the sapphire polishing solution in this application to polish the sapphire. The sapphire polishing solutions obtained in Examples 1 to 7 and Comparative Examples 1 to 2 were used to polish the sapphire respectively: 2L of sapphire polishing solution was taken and diluted with pure water at a dilution ratio of 1:10.

[0136] Polishing conditions: Polishing machine MZS36B-4P-5M (double-sided), polishing pad Suba 800 (20*20mm groove), pressure 300g / cm² 2 The polishing speed was 35 rpm, the polishing fluid flow rate was 2 L / min, the polishing time was 2 h, and the polishing object was 9 4-inch sapphire wafers.

[0137] The polishing effect of the sapphire polishing slurry was tested, and the results are shown in the table below:

[0138] serial number Removal rate μm / h Roughness Ra (nm) Example 1 9.2 0.267 Example 2 8.5 0.288 Example 3 8.8 0.275 Example 4 7.9 0.298 Example 5 7.5 0.306 Example 6 7.7 0.300 Example 7 7.1 0.309 Comparative Example 1 6.3 0.324 Comparative Example 2 6.1 0.323

[0139] Test result data explanation:

[0140] 1. In terms of removal rate, the alumina powder particles and content of Example 1 and Comparative Example 1 are equal. The removal rate of Example 1 is 9.2 μm / h, which is higher than that of Comparative Example 1 (6.3 μm / h). The removal rates of other examples are above 7.1 μm / h. Among them, the sapphire polishing solution in Examples 1-3, which is a combination of nonionic cellulose ether and polysaccharide with rigid double helix, low charge, and acetyl-free structural characteristics, has a higher removal rate than that in Examples 4-7, which use the above two types of suspending agents alone.

[0141] 2. In terms of roughness, the alumina powder particles and content of Example 1 and Comparative Example 1 are equal. The roughness of Example 1, at 0.267 nm, is better than that of Comparative Example 1, at 0.324 nm. The roughness of the other examples is below 0.309 nm. Among them, the roughness of the sapphire polishing fluid in Examples 1-3, which are a combination of nonionic cellulose ether and a polysaccharide with rigid double helix structure, low charge, and no acetyl, is better than that in Examples 4-7, which use the above two types of suspending agents alone.

[0142] It is evident that the sapphire polishing slurry of the present invention can achieve high polishing removal efficiency and excellent surface quality (low roughness Ra) on sapphire wafers under strong alkaline and high ionic strength conditions.

[0143] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A sapphire polishing slurry, characterized in that, The sapphire polishing slurry comprises the following components in parts by weight: 20-30 wt% alumina powder, 0.1-1 wt% dispersant, 0.01-1 wt% suspending agent, 1-10 wt% pH adjuster, 0.1-3 wt% lubricant, and the balance being water; the suspending agent is selected from one or more of nonionic cellulose ethers and polysaccharides with the structural characteristics of rigid double helix, low charge, and no acetyl.

2. The sapphire polishing slurry according to claim 1, characterized in that, The suspending agent comprises a mixture of nonionic cellulose ether and polysaccharides that possess structural characteristics of rigid double helix, low charge, and no acetyl. And / or, the polysaccharide possessing the structural characteristics of rigid double helix, low charge, and acetyl-free is selected from one or more of the following: gentian gum and its modified products, gentian gum and its modified products, and gentian gum and its modified products; And / or, the nonionic cellulose ether is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl cellulose, and hydroxyethyl ethyl cellulose; And / or, the alumina powder is α-alumina; And / or, the D of the alumina powder 50 The diameter is 0.3–3 μm, D 100 <10μm.

3. The sapphire polishing slurry according to claim 1, characterized in that, The lubricant is selected from one or more of PEG, polyglycerol-10, triethylene glycol, glycerin, triethanolamine borate, and diethanolamine borate; And / or, the dispersant is selected from one or more of sodium polyacrylate, acrylic acid-maleic acid copolymer, sodium hexametaphosphate, and sodium tripolyphosphate; And / or, the pH adjuster is selected from one or more of potassium hydroxide, sodium hydroxide, and triethanolamine; And / or, the pH value of the sapphire polishing solution is 12-14.

4. A method for preparing a sapphire polishing slurry as described in any one of claims 1 to 3, characterized in that, The preparation method includes the following steps: stirring and mixing the raw material components.

5. The preparation method according to claim 4, characterized in that, The mixing sequence is as follows: first, mix water, alumina powder, dispersant, and lubricant evenly; then add an aqueous solution of suspending agent and mix evenly; then add a pH adjuster and mix evenly to adjust the pH of the mixture to 12-14. And / or, the linear velocity of the stirring mixture is 3-10 m / s.

6. The preparation method according to claim 5, characterized in that, The method for preparing the aqueous solution of the suspending agent includes: dispersing the suspending agent in water, and fully hydrolyzing and swelling it; And / or, the concentration of the aqueous solution of the suspending agent is 0.5–2 wt%; And / or, after adjusting the pH of the mixture to 12-14, the process also includes further steps of dispersion, filtration, and filling.

7. The preparation method according to claim 5, characterized in that, The aqueous solution containing the suspending agent should be mixed thoroughly for 45–75 minutes. And / or, the pH adjuster is added and mixed for 45–75 minutes.

8. The preparation method according to claim 6, characterized in that, The linear velocity of the suspending agent dispersed in water is 3-10 m / s; And / or, the continued dispersion time is 90 to 180 minutes.

9. The application of a sapphire polishing slurry as described in any one of claims 1 to 3 in polishing sapphire.

10. Use of a suspending agent in improving the suspension properties of sapphire polishing fluid, said suspending agent being selected from one or more of nonionic cellulose ethers and polysaccharides that possess structural characteristics of rigid double helix, low charge, and no acetyl.